Concept-Oriented Reading Instruction (CORI) Strategy in Improving Students’ Reading Comprehension - Liska Oktavia; Fetriani; Ririn Putri Ananda; Kiagus Baluqiah (Teaching English and Language Learning English Journal, 2022)
The aim of this research was to know whether has an effect of Concept-Oriented Reading Instruction (CORI) Strategy in improving students’ reading comprehension at second semester English Study Program of UMB. This research is a quasi experimental research. In this research, the population on the research included all second semester English Study Program of UMB in academic year 2021/2022. There were 32 students for the class. One class is an experiment class, it used concept-oriented reading intruction (CORI) and another without using concept-oriented reading intruction (CORI). The instrument on this research was reading test and aimed to measure students’ reading comprehension. The researcher used essay form with total 10 questions. Those question have been valid and reliable since it was adopted from Reading for Intermediate textbook. The finding of the research showed that there is a significant difference in post-test results between the group that was taught with CORI strategy and the group that was taught with conventional technique at second semester English Study Program Students of University Muhammadiyah Bengkulu. Moreover, the finding of this research confirmed the hypothesis of this research. Keywords : Concept-Oriented Reading Instruction (CORI) Strategy, Reading Comprehension